The development of a training program for the prevention of knee injuries in female athletes
Cincinnati Sportsmedicine Research and Education Foundation: Females are five times more likely than males to sustain an anterior cruciate ligament injury. More than ten years ago, we and others recognized the exceptionally high frequency of anterior cruciate ligament (ACL) injuries occurring in female athletes. A number of studies have unequivocally demonstrated that female athletes that participate in jumping and cutting sports are about five times more likely to sustain serious knee injuries than males. The majority of these serious knee injuries are non-contact injuries. Tens of thousands of serious knee injuries occur in female collegiate and high school athletics each year. The majority of these injuries are non-contact injuries. In fact, they often occur while landing from a jump or pivoting when running. Dr. Frank Noyes reported in the early eighties that four-fifths of ACL injuries occur via a non-contact mechanism, and the majority of these occur while landing from a jump. In a rigorous study of the incidence of injury in soccer, Dr. Thomas Lindenfeld and Dr. Frank Noyes at the Cincinnati Sportsmedicine Orthopaedic Center reported that the incidence of serious knee injury was approximately six-fold higher in female than male players when normalized per player-hour. In a biomechanical study conducted in this laboratory, we were the first to demonstrate that decreased neuromuscular strength and coordination in the musculature which stabilizes the knee joint may be responsible for this increase in injuries. This study showed that males activate their knee flexors at three times the level of females during landing from a jump. It also showed that the female hamstrings are significantly weaker than males prior to training with the jump training program we developed, Cincinnati Sportsmetrics. After training, females showed increased hamstrings strength and decreased dangerous forces at the knee.